استخدام الأغاني الأمثلة التصريفية لزيادة الدوافع في التعلمية المدرسة العالية سونان أمفيل جومبانج - Ahmad Aufal Khoiri; Lailatul Qomariyah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2023)
Arabic is a language that some people consider difficult because there are many branches that need to be learned. The importance of learning Arabic as a language between Islamic schools and non-Islamic schools is partly because Arabic has grammatical richness. This is found in the science of syntax and morphology. The process of learning morphology is generally done by memorizing. One of the problems that occur in learning morphology is the difficulty of memorizing and applying words with all their changes. The solution introduced to facilitate memorization, Wazan is delivered in musical form. This happens as in learning the rules of conjugation with a conjugation example book. This method is a way to facilitate learning (memorization) as well as a solution to overcome learning problems that stem from language barriers. The keywords are memorization and transmission through musical intelligence or multiple intelligences, namely learning with songs. By using the song method, students can understand the basic concepts of morphology to learn language properly or correctly.